Preparation and Evaluation of Cellulose Acetate Phthalate and Ethyl cellulose based Microcapsules of Diclofenac Sodium using Emulsification and Solvent-Evaporation Method - Rahman, Md Mominur; Islam, Md Saiful; Sharmin, Nahid; Chowdhury, Jakir Ahmed; Jalil, Reza-ul (Dhaka University Journal of Pharmaceutical Sciences, 2011)
Diclofenac sodium (DS) microspheres were prepared with two different polymers, ethyl cellulose (EC) and cellulose acetate phthalate (CAP). Emulsification-solvent evaporation method was used to prepare the microspheres. Liquid paraffin containing 1.5% (w/w) span 80 was the external phase and acetone-polymer solution was the internal phase. EC and CAP, both as single and as mixture, were used to encapsulate DS. EC microspheres were more spherical in shape and showed more entrapment efficiency than CAP microspheres. The size of the microspheres varied between 560-920 μm and as high as 90% loading efficiency was obtained. In vitro release study was carried out in 0.1 N hydrochloric acid solution (pH 1.2) for first 2 hours followed by in phosphate buffer solution (pH 6.8) for next 4 hours. After first 2 hours of dissolution in 0.1 N hydrochloric acid, EC microspheres released 24% of DS whereas CAP microspheres released only 2% DS. After 4 hours of dissolution in phosphate buffer, 60% DS was released from EC microspheres and almost all drug was released from CAP microspheres. Combination of EC and CAP showed more sustaining action than the individual polymer in both the dissolution media. DS release from EC microspheres followed Higuchi model whereas CAP microspheres followed first order model. Key word: Diclofenac sodium; microsphere; Ethyl cellulose; Cellulose acetate pthalate DOI: 10.3329/dujps.v9i1.7428 Dhaka Univ. J. Pharm. Sci. 9(1): 39-46 2010 (June)